Carbon footprint analysis considering transportation activities based on life cycle assessment: the case of tobacco industries of China - Jian, Yonghan; Liu, Dongxiao; Su, Zhiling; Xiao, Jianqiang; Zhang, Guowei (Frontiers in Environmental Science, 2025)
IntroductionWith the proposal of China’s “Dual Carbon” targets, how to measure carbon footprint in detail is particularly important. However, the current carbon footprint measurement mainly focuses on the production process, ignoring the high carbon emission caused by the transport phase. In this paper, we take the tobacco industry as the research object, and include the transport phase in the carbon footprint measurement.MethodsBased on the existing statistical data, this paper adopts the Life Cycle Assessment (LCA) to comprehensively measure and analyze the carbon footprint of China’s tobacco industry from 2011 to 2020.ResultsThe results show that the average carbon footprint per hectare of the tobacco industry is about 21.57 tons of carbon dioxide equivalent, while showing a slowly increasing trend in recent years. In terms of linkage and raw material composition, the carbon footprints of fertilizer application, agricultural film input, initial curing and air transportation is relatively high, accounting for 8.2%, 66% and 4.7% of the total emissions respectively. Combined with the cost of tobacco planting, it can be found that Yunnan, Guizhou and Jiangxi are facing the problems of high input, low output and high emission.DiscussionThe results are of great significance in promoting low-carbon tobacco growing and green transport.